PENGARUH STAKEHOLDER PRESSURE DAN DEWAN KOMISARIS INDEPENDEN TERHADAP KUALITAS SUSTAINABILITY REPORT - Putri, Rahmadani Desita; Pratama, Febrial; Muslih, Muhammad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Sustainability Report is a report expressed by the company as a means to communicate economy, environmental, and social aspects to its stakeholders. A Sustainability Report is expected to have good quality. In fact, there are still many companies that are not maximal in publishing Sustainability Report quality, especially in companies listed in the LQ45 index in 2016 to2019. The purpose of this research is to determine the effect of stakeholder pressure and independent board of commissioners on the Sustainability Report quality on companies listed in the LQ45 index for the period 22016-2019. This research is a descriptive research using purposive sampling in sampling techniques so that a total of 64 samples were obtained from companies listed in the LQ45 index during the period 2016-2019 with the regression model used is data panel regression model. The results showed that pressure from the environment as stakeholders positively influence the sustainability report quality. While the pressure from employees and shareholder as stakeholders has no effect on the Sustainability Report quality. The independent board of commissioners has no effect on the sustainability Report quality.